Progesterone Receptor Gene Polymorphism Promoter Region +331G/A Increases Risk of Endometriosis - Alkaf, Syifa; Chakra, Aerul; Said, Usman; Saleh, Irsan (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To identify relationship between progesterone receptor gene polymorphism promoter region +331G/A with the risk of endometriosis. Method: An observational case-control study. Population are women with endometriosis and/or adenomyosis who have been performed laparotomy/laparoscopy at Obstetrics and Gynecology Department Dr. Mohammad Hoesin General Hospital Palembang, January-November 2013. Subjects fulfilled inclusion criteria, given informed consent and performed blood sampling continued by PCRRFLP. Results were divided into A/A genotype (homozygote mutant), G/A (heterozygote mutant), and G/G (homozygote wild type). Data were analyzed by SPSS 21.0 version. Result: PCR-RFLP results for+331G/A genotype were 26 (54.1%) in case group and 14 (26.4%) in control. +331A/A genotype was not found in both groups. There was significant increase risk of endometriosis in women carrying genotype +331G/A to those with genotype +331G/G with OR 3.29 (p